1998
DOI: 10.1039/a802772b
|View full text |Cite
|
Sign up to set email alerts
|

Alumina: an Efficient and Reusable Catalyst for the Oxidative Coupling of Thiols with DMSO

Abstract: An inexpensive combination of common laboratory reagents, dimethyl sulfoxide (DMSO) and chromatographic neutral alumina, gives an efficient, selective, and high-yielding oxidation of aromatic, aliphatic and alicyclic thiols to the corresponding disulfides in excellent yields under relatively mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Evidence of the attack of a soft nucleophile It was also found that the reactions of ArS(ArSSAr) + (1) (Ar = p-FC 6 H 4 ) with alkynes gave the corresponding diarylthiosubstituted compounds, when a soft nucleophile such as allylsilane 6 and triethylamine was used as a quenching nucleophile (Table 2). The reactions were highly stereoselective (except for formation of 19), and the stereochemistry of the products were identified as E-isomers by comparison of the NMR spectra with those reported in the literature. ArS(ArSSAr) + having various substituent(s) on the aromatic ring could also be generated and accumulated by the electrochemical oxidation of the corresponding ArSSAr in CH 2 Cl 2 at −78 o C. Their reactions with diphenylethyne took place smoothly to give the corresponding (E)-1,2-diarylthio-1,2-diphenylethenes (Table 3).…”
Section: Scheme 4 Existence Of the Equilibriummentioning
confidence: 94%
See 1 more Smart Citation
“…Evidence of the attack of a soft nucleophile It was also found that the reactions of ArS(ArSSAr) + (1) (Ar = p-FC 6 H 4 ) with alkynes gave the corresponding diarylthiosubstituted compounds, when a soft nucleophile such as allylsilane 6 and triethylamine was used as a quenching nucleophile (Table 2). The reactions were highly stereoselective (except for formation of 19), and the stereochemistry of the products were identified as E-isomers by comparison of the NMR spectra with those reported in the literature. ArS(ArSSAr) + having various substituent(s) on the aromatic ring could also be generated and accumulated by the electrochemical oxidation of the corresponding ArSSAr in CH 2 Cl 2 at −78 o C. Their reactions with diphenylethyne took place smoothly to give the corresponding (E)-1,2-diarylthio-1,2-diphenylethenes (Table 3).…”
Section: Scheme 4 Existence Of the Equilibriummentioning
confidence: 94%
“…Trifluoromethanesulfonic acid (TfOH) was purchased from Nacalai and was used without further purification. ArSSAr (Ar = p-FC 6 H 4 ) was prepared according to the procedures in the literatures, 19 and identified by the comparison of its spectral data with that of authentic sample. 20 (2,4-difluoropheny) disulfide.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that most of the previously reported methods for the oxidation of thiols use synthesized or toxic reagents and/or suffer from other disadvantages such as long reaction time and low yields, [3][4][5][6][7][8][9] but this method uses a readily available reagent and additionally offers the advantages of high yields, short reaction time, no side reactions, mild reaction conditions, a solid state reaction and simple isolation of the products. Consequently, this methodology should represent a good addition to list of methods already available for this purpose.…”
Section: Methodsmentioning
confidence: 99%
“…Sweetening of catalyst poisons thiols to low volatile disulfides in oil industries and industrial applications of disulfides in vulcanization of rubbers and elastomers led us to investigate the introduction and applications of new member of this category of reagents in oxidation of thiols to the corresponding disulfides. 2 The main type of these reactions is the oxidation of thiols in the presence of manganese dioxide, 3 dichromates, 4 borohydride exchange resin, 5 DMSO/alumina reagent, 6 CBr 4 /solid K 2 CO 3 /18-crown-6/benzene 7 and NaIO 3 /alumina 8 and tetramethylammonium fluorochromate. 9 However, some of the reported reagents suffer from disadvantages such as instability, hygroscopicity, low selectivity, long reaction time, difficulty of preparation and need for a large excess of the reagent.…”
Section: Introductionmentioning
confidence: 99%
“…The main type of these reactions is the oxidation of thiols in the presence of molecular oxygen [3], DMSO [4], using borohydride exchange resin [5], DMSO/alumina reagent [6], CBr 4 / solid K 2 CO 3 /18-crown-6/benzene [7] and NaIO 3 /alumina [8].…”
Section: Introductionmentioning
confidence: 99%